Individual skills based volunteerism and life satisfaction among healthcare volunteers in Malaysia: role of employer encouragement, self-esteem and job performance, a Cross-sectional study - Chanthiran Veerasamy; Murali Sambasivan; Naresh Kumar (2013)
The purpose of this paper is to analyze two important outcomes of individual skills-based volunteerism (ISB-V) among healthcare volunteers in Malaysia. The outcomes are: job performance and life satisfaction. This study has empirically tested the impact of individual dimensions of ISB-V along with their inter-relationships in explaining the life satisfaction and job performance. Besides, the effects of employer encouragement to the volunteers, demographic characteristics of volunteers, and self-esteem of volunteers on job performance and life satisfaction have been studied. The data were collected through a questionnaire distributed to 1000 volunteers of St. John Ambulance in Malaysia. Three hundred and sixty six volunteers responded by giving their feedback. The model was tested using Structural Equation Modeling (SEM). The main results of this study are: (1) Volunteer duration and nature of contact affects life satisfaction, (2) volunteer frequency has impact on volunteer duration, (3) self-esteem of volunteers has significant relationships with volunteer frequency, job performance and life satisfaction, (4) job performance of volunteers affect their life satisfaction and (5) current employment level has significant relationships with duration of volunteering, self esteem, employer encouragement and job performance of volunteers. The model in this study has been able to explain 39% of the variance in life satisfaction and 45% of the variance in job performance. The current study adds significantly to the body of knowledge on healthcare volunteerism.